Green hopes: Spatial and Settlement Development Operative Programs in the Programming Period 2014-2020 (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
The problem of sustainability has become one of the most crucial issues on the highest European levels. The European Parliament has voiced its support of action plans and their elements regarding sustainable consumption and production. One practical manifestation is the fact that in the programming period 2014-2020 sustainable development appears as a requirement of the European Union (EU in further text) subsidy systems. The access to subsidies is not limited to a branch-wise differentiation, but is also available on a regional, local basis. This was what smart specialisation prepared. The financial and structural frame is provided by the Spatial and Settlement Operative Program (TOP in further text) which provides local communities calls on a regional selection. The further aim, the reduction of administrative burdens and a more simplified call process, could so far not be achieved, as there was rather an increase in the administrative burdens of local governments. Local governments can often only fulfil this complicated criteria-system by involving external experts. The research was aimed at a project about a TOP-based “green town establishment” on the example of European small town. In the followings, the substantiation of the needs-measurement and utilisation plan and the related primary and secondary research will be presented. The aim of the research was the analysis of the substantiation of the project and the measurement of its cohesion with other – urban – strategic documents.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.